PENGARUH STRATEGI INKUIRI SOSIAL BERBANTUAN POWER POINT TERHADAP HASIL BELAJAR IPS SISWA KELAS V SD - ., Ni Luh Putu Muri Adnyani; ., Ida Bagus Gede Surya Abadi, SE., M.Pd; ., Drs. I Wayan Darsana,M.Ed (MIMBAR PGSD Undiksha, 2014)
Penelitian ini bertujuan untuk mengetahui perbedaan yang signifikan hasil belajar IPS antara siswa yang dibelajarkan melalui strategi pembelajaran inkuiri sosial berbantuan media power point dengan siswa yang dibelajarkan secara konvensional pada kelas V SD Gugus II Mengwi Badung tahun ajaran 2013/2014. Jenis penelitian ini adalah eksperimen semu, dengan desain nonequevalent control group design. Populasi penelitian ini yaitu seluruh siswa kelas V SD gugus II Mengwi Badung tahun ajaran 2013/2014. Sampel penelitian ditentukan melalui teknik purposive random sampling untuk menentukan kelas eksperimen dan kelas kontrol. Kelas eksperimen adalah kelas VB SD No. 1 Buduk yang berjumlah 37 siswa dan kelas kontrol adalah kelas V SD No. 2 Buduk yang berjumlah 43 siswa. Data hasil belajar IPS dikumpulkan menggunakan metode tes, kemudian dianalisis menggunakan uji-t. Hasil analisis data menunjukkan terdapat perbedaan yang signifikan hasil belajar IPS antara siswa yang dibelajarkan melalui strategi pembelajaran inkuiri sosial berbantuan media power point dengan siswa yang dibelajarkan secara konvensional pada kelas V SD Gugus II Mengwi Badung tahun ajaran 2013/2014. Hal tersebut dibuktikan dari t_hitung = 3,35 > ttabel(α=0,05,78)= 2,000 dengan dk = 37 + 43 – 2 = 78, serta taraf signifikansi 5%, sehingga H0 ditolak dan Ha diterima. Selain itu, nilai rata-rata kelas eksperimen X ̅ = 81,07 > X ̅ = 73,29 pada kelas kontrol. Sehingga, dapat disimpulkan bahwa penerapan strategi pembelajaran inkuiri sosial berbantuan media power point berpengaruh terhadap hasil belajar IPS siswa kelas V SD gugus II Mengwi Badung tahun ajaran 2013/2014. Kata Kunci : strategi pembelajaran, inkuiri sosial, media power point, hasil belajar IPS. This research aimed to determine a significant difference in social science learning’s outcomes between the students who learned through the social inquiry learning strategy assisted by power point media and the students who learned through the conventional teaching method in fifth grade of elementary school Cluster II Mengwi, Badung in 2013/2014 academic year. This research was a quasi experimental research that used none-equivalent control group design. The populations of this research were all the fifth grade students in elementary school Cluster II Mengwi, Badung in 2013/2014 academic year. The samples of this research were determined through the purposive random sampling technique to define the experimental class and the control class. The experimental class was the fifth grade B of elementary school number 1st Buduk which has 37 students and the control class was the fifth grade students of elementary school number 2nd Buduk which has 43 students. The students’ results in the social science subject in this research were collected through the test method and it would be analyzed through the t-test. The result of the data analysis shows that there are a significant difference in the social science learning’s outcomes between the students who learn through the social inquiry learning strategy assisted by power point media and the students who learn through the conventional teaching method in fifth grade of elementary school Cluster II Mengwi, Badung in 2013/2014 academic year. This result can be proved through t_value = 3,35 > ttable(α=0,05,78) = 2,000 with df = 37 + 43 – 2 = 78, and also a significant level up to 5 %. Therefore, H0 is rejected and Ha is accepted. In addition, the mean value of the experimental class X ̅ = 81,07 > X ̅ = 73,29 for control class. So, it can be concluded that the implementation of the social inquiry learning strategy assisted by power point media has an effect on the social science learning’s outcomes of the fifth grade students in elementary school Cluster II Mengwi, Badung in 2013/2014 academic year.keyword : learning strategy, social inquiry, power point media, the social science learning outcomes.